2015
DOI: 10.1007/s13762-015-0800-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation, evaluation and prediction modeling of river water quality properties (case study: Ireland Rivers)

Abstract: In this analysis, three input parameters temperature, pH and electrical conductivity were chosen due to their easy and less costly measurement technique, and a package of six models were presented for estimating the concentrations of dissolved oxygen, DO percentage, biological oxygen demand, chloride, alkalinity and total hardness. 3001 data sets (a 3001 9 8 data array) were used to training the models. The models have been tested in order to verify their prediction values, and the resulted R factor (the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…According to the number of times the observations are greater than the mean error as discussed by Ritter and uñoz-Carpena (2013), models 1, 2, 3 and 4 can be classified as good. The evaluation statistics indicated in Table 4 concurs with those found by Salami and Ehteshami (2015) where R 2 of 0.82, 0.85 and 0.92 for chloride, alkalinity and hardness respectively were obtained for prediction of dissolved oxygen. However, the RMSE values in Table 4 are slightly higher than those found by Zhang et al (2010) temperature, BOD and ammonium had higher correlations with DO.…”
Section: Resultssupporting
confidence: 85%
“…According to the number of times the observations are greater than the mean error as discussed by Ritter and uñoz-Carpena (2013), models 1, 2, 3 and 4 can be classified as good. The evaluation statistics indicated in Table 4 concurs with those found by Salami and Ehteshami (2015) where R 2 of 0.82, 0.85 and 0.92 for chloride, alkalinity and hardness respectively were obtained for prediction of dissolved oxygen. However, the RMSE values in Table 4 are slightly higher than those found by Zhang et al (2010) temperature, BOD and ammonium had higher correlations with DO.…”
Section: Resultssupporting
confidence: 85%
“…They applied a self-organizing map (SOM), a stratified method, to construct a topological map to visualize the clustered input variables, thereby ensuring that the statistical properties of the subsets were similar. Levenberg-Marquardt algorithm [24,[136][137][138][139] and Bayesian methods were conducted to train the network. Results showed that ANN models could achieve high accuracy.…”
Section: Artificial Neural Network Models For Water Quality Predictionmentioning
confidence: 99%
“…Automated detection of pipe bursts approach came to the limelight, using different Artificial Intelligence (AI) tools to predict the leakage prior to its taking place with some variables like pressure and flow signal value [45]. AI has shown significance capability to deal with missing data, decreases the cost of testing [46][47][48], can easily classify the point source of the leakage [49], and predict the life of the distribution system components [50]. These advantages make the potential of AI models useful in developing countries where there are lacks of uniform and regular data, funding for data collection and testing, advanced sensors to pinpoint the leakage sources, and lack of regular maintenance system.…”
Section: Recommendationsmentioning
confidence: 99%